Ileocolic intussusception due to a lipoma of the ileum: a case report - Luján Carpio, Elmer Julio César (2025)
Intussusception is an uncommon cause of acute surgical abdomen in adults. It is more common in pediatric patients, who usually present with classic symptoms including rectal bleeding, abdominal distension, and nausea. In contrast, in adult cases often present with nonspecific symptoms, such as abdominal pain and distension, making diagnosis more challenging. We present the case of a 41-year-old female patient, with no significant medical or surgical history, who was admitted with abdominal pain, vomiting, abdominal distension, and inability to pass flatus. Symptom intensity gradually increased. Physical examination revealed a distended abdomen with decreased bowel sounds, abdominal tenderness predominantly in the right iliac fossa, where a palpable mass was also noted. No signs of peritoneal irritation were observed. Contrast-enhanced abdominal CT confirmed intestinal intussusception at the level of the ascending colon, with proximal dilation of bowel loops and collapse of distal loops, without evidence of pneumoperitoneum or free f luid. An emergency exploratory laparotomy was carried out, confirming ileocolic intussusception. Surgical management included a right hemicolectomy and primary end-to-side ileotransverse anastomosis performed with a circular stapler. Postoperatively, the patient had a favorable clinical course during hospitalization, with no fever, improved tolerance of oral intake, adequate pain management, and was discharged without major complications. Histopathological examination identified a polypoid tumor in the ileal segment, located 15 cm from the proximal surgical margin, corresponding to a pedunculated lipoma of the ileum associated with transmural necrosis, which had caused the ileocolic intussusception.